NLO corrections to the pair production of supersymmetric particles - Obikhod, T.V.; Verbytskyy, A.A. (Вопросы атомной науки и техники, 2014)
The analysis of recent experimental data received from LHC (CMS) restricts the range of MSSM parameters. Using computer programs SOFTSUSY, SDECAY the mass spectrum and partial width of superpatners are calculated. With the help of computer program PROSPINO the calculations of the next-to-leading order (NLO) corrections to the production cross sections of superpartners are made. With the help of computer program PYTHIA the NLO corrections on differential distributions of pT and η for squarks and gluino are represented.